Quality Improvement in Management of Acute Coronary Syndrome: Continuing Medical Education and Peer Coaching Improve Antiplatelet Medication Adherence and Reduce Hospital Readmissions. Issue 3 (September 2017) - Larkin, Amy; LaCouture, Michael; Geissel, Kathleen; Barr, Peri; Bates, Eric R.; Cannon, Christopher P.; Bhatt, Deepak L.
Abstract : Background: Reducing hospital readmissions and improving patient adherence to antiplatelet medications after an acute coronary syndrome (ACS) event are important goals for improving patient health and decreasing healthcare costs. Nearly half of patients will have a secondary event within 1 year of the initial ACS event. Quality improvement (QI) initiatives that include continuing medical education and peer coaching may improve physician practice patterns and, therefore, patient outcomes. Methods: This study evaluated the impact of a QI initiative on antiplatelet (P2Y12 inhibitor) medication adherence (measured via pharmacy fill rates postdischarge) and hospital readmissions. Results: Notable physician performance and patient-level changes included significant increases in antiplatelet medication counseling at hospital discharge (30%–57%; P < 0.0001), in P2Y12 inhibitor prescribing at hospital discharge (76%–84%; P = 0.02), and in patient fill rates for branded P2Y12 inhibitors (72%–100%; P = 0.0001). There were numerical trends toward lower rates of ACS-related rehospitalizations at 60 days postdischarge (from 11% to 7%; P = 0.15) and of all-cause rehospitalizations at 60 days (from 20% to 14%; P = 0.10). Conclusion: Important in the rapidly evolving landscape of quality healthcare, QI involving continuing medical education and peer coaching demonstrably impacted physician performance and patient outcomes after an ACS event.